KEANEKARAGAMAN SERANGGA PADA PERKEBUNAN KAKAO (Theobroma cacao L.) YANG DIAPLIKASI INSEKTISIDA DAN TANPA INSEKTISIDA - Latip,Flora Pasaru, Hasriyanti, Dedis (AGROTEKBIS, 2015)
The study objective to determine the insect diversity in cocoa farm (Theobroma cacao L.) affected by insecticide application. The research was conducted in August - December 2013, at Gio and Karya Abadi village, Parigi Moutong, Sulawesi. Insect identification was done in the Plant Pests and Diseases Laboratory, Agriculture Faculty of Tadulako University. The study used purposive sampling, sampling the insects in cacao farm which had been applied with and without- insecticide. The study area for insecticide and non insecticide treatments are namely 1 ha of each and it was divided into 5 plots, totally having 10 plots for observation. In each plot insects were collected by using a sweep net, pitfall and yellow traps. Insect observations performed at once a week, overall was 3 weeks. The result showed that diversity of insect is significantly higher in the farm without insecticide than the insecticide application, namely 1535 and 1177 insects, respectively. The non insecticide farm resulted to 19 Families from 8 Ordo and the insecticide? farm have only 17 families and also 8 Ordo. Therefore, the diversity index (H') is higher in non- insecticide than the insecticide application.